Children’s self-image following abuse, development of resilience and family context impact: A Clinical Psychodynamic approach. - Stavrou, Pilios Dimitris (Advances in Social Sciences Research Journal, 2018)
Objective The purpose of this research was to study the consequences of intra-family physical abuse by the parent(s) on the development of children’s self-image, i.e. on the way they perceive themselves. Moreover, a second objective was to investigate if resilience can occur due to a new environment, and especially a new family, which will provide security and warm to the abused children. Methods The sample consisted of two young children. Both of them were seen three different times during sixteen months. The first evaluation, which happened with the use of projective tests, similarly to the other two, took place two months after the children were placed into a host family, the second four months after the first session and the third one a year after the second session. The projective tests used were: "The Human Figure Drawing (HFD)", "Patte Noire" (" Black Foot"), "Children Apperception Test (C.A.T.)", "The Family Drawing Test" and the "House-Tree-Person test (HTP)". Results The tests revealed that the emotional deprivation caused by the abusive behavior of the biological parents resulted in the development of a negative self-image. Furthermore, children with failing parenting models who were placed into a host family after their abuse and met one or more "resilience guardians", who have been identified as positive identifiers, presented behaviors characteristic of resilience. Keywords: children’s abuse, self-image, resilience, familial context